Changes in Young Adults’ Alcohol and Marijuana Use, Norms, and Motives From Before to During the COVID-19 Pandemic - Graupensperger, Scott; Fleming, Charles B.; Jaffe, Anna E.; Rhew, Isaac C.; Patrick, Megan E.; Lee, Christine M. (Journal of adolescent health, 2021)
Alongside the SARS-CoV-2 virus, the COVID-19 pandemic is associated with several secondary health effects. There is concern for increased substance use motivated by coping with stress, anxiety, depression, and boredom–all of which may be elevated during the pandemic. The current study examined intraindividual changes (from pre-COVID to during COVID) in young adults’ alcohol and marijuana use, perceptions of peers’ use (i.e., norms), and motives for use. A community sample of young adults (N = 572; Mage= 25.14; 60.8% women) was recruited in Washington State. By using a repeated-measures design, data were collected prior to the COVID-19 pandemic (January 2020) and again during the initial acute phase of the pandemic (April/May of 2020). Young adults, on average, increased alcohol use frequency but decreased the amount consumed per drinking occasion. No changes in marijuana use were identified. Young adults (on average) perceived that peers had increased the frequency and total amount of alcohol use and perceived that peers were engaging in heavier marijuana use than prior to COVID-19. For alcohol use motives, there was a significant increase in depression coping motives and significant decreases in social, enhancement, and conformity motives. Boredom motives for marijuana use significantly increased, while celebration motives decreased. Using a prospective design with a sample initially recruited in Washington State, these data indicate that (a) young adults’ patterns of alcohol use may have changed, (b) young adults tend to think that peers are engaging in heavier alcohol/marijuana use than before the pandemic, and (c) motives for using alcohol/marijuana may have changed during the pandemic.